(untitled) (Journal of the College of Education for Women, 2019)
We deal with this essay about religious mystic poetry of Atika Al-Khazraji. We think she imitates Rabia Al-Adawiyya. We do not deny that ourpoetess lived in a conservative society although she lives in reality a liberallife, so she tries to satisfy her society. In fact these mystic poems are purelove. Poems in men.This double standard behavior is quite clear in women’s poems in theArab world of this era.